A Study of Unlawful Acts in the Indonesian Legal System - Hutabarat, Theofilus Immanuel Pastika; Wijaya, Andika; Sangalang, Rizki Setyobowo; Hutapea, Charles (Manunggal Halim Jaya, 2026)
Unlawful acts are a fundamental concept in Indonesian civil law as stipulated in Article 1365 of the Civil Code as the basis for liability for losses incurred to other parties. Along with the development of society, the meaning of unlawful acts is not only limited to violations of the law, but also includes violations of subjective rights, legal obligations, moral norms, and the principle of propriety. This study aims to analyze the concept and application of unlawful acts in Indonesian civil law by using normative legal research methods through legislative, conceptual, and case approaches. The results of the study show that unlawful acts play an important role in legal protection, but there are still differences in judges' interpretations of its elements that have the potential to cause legal uncertainty. Therefore, consistency of interpretation and strengthening of jurisprudence is needed to realize justice, legal certainty, and utility.